Marketing places : Reading (Fulbrright, 2001)
The hidden key to vigorous economic development, the author argues, is strategic marketing of places by rebuilding infrastructure, creating a skilled labour force, stimulating local business entrepreneurship and expansion, developing strong public/private partnerships, identifying and attracting "place compatible" companies and industries, creating distinctive local attractions, building a service-friendly culture, and promoting these advantages effectively. Strategic marketing of places requires a deep understanding of how "place buyers" - tourists, new residents, factories, corporate headquarters, investors - make their place decisions. With this understanding, "place sellers" - economic development agencies, tourist promotion agencies, mayor's offices - can take the necessary steps to compete aggressively for place buyers.
Keywords: Marketing,Industrial promotion,Industrial location